Pragmatic visualizations for Roassal: a Florilegium - Mathieu Dehouck; Usman Bhatti; Alexandre Berge; Stéphane Ducasse (IWST'13: Proceedings of the International Workshop on Smalltalk Technologies, 2013)
Software analysis and in particular reverse engineering often involves a large amount of structured data. This data should be presented in a meaningful form so that it can be used to improve software artefacts. The software analysis community has produced numerous visual tools to help understand different software elements. However, most of the visualization techniques, when applied to software elements, produce results that are difficult to interpret and comprehend. This paper presents five graph layouts that are both expressive for polymetric views and agnostic to the visualization engine. These layouts favor spatial space reduction while emphasizing on clarity. Our layouts have been implemented in the Roassal visualization engine and are available under the MIT License.